The use and impact of repeated questions in diagnostic child abuse assessment interviews. Issue 3 (4th May 2022) - Macleod, Emily; Hobbs, Linda; Admiraal, Anita; La Rooy, David; Patterson, Tess
Abstract : There is limited research regarding the use of repeated questions and the subsequent response from children in real-world forensic contexts. We analysed 71 transcripts of diagnostic assessments in which 3- to 6-year-olds were assessed for suspected abuse experiences. On average, 6% of interviewer questions were repeated, and 47% of the repeated questions were abuse-related. The majority (65%) of the repeated questions were directive, but 33% of the repeated questions contained implicit assumptions. Implicit assumption questions were more likely to be abuse-related. Interviewers repeated questions when the child failed to answer due to playing (31%), for no apparent reason (26%) or for clarification purposes (29%). Children most commonly responded to repeat questions by providing new information (64%), not responding at all (19%) or repeating information (12%). We recommend that interviewers avoid the use of suggestive and repeated questions that contain implicit assumptions in relation to assessment of suspected child abuse.